A new species of the genus Protohyale Bousfield & Hendrycks, 2002 (Crustacea, Amphipoda, Hyalidae) from Covelong, Chennai, India - Raut, Shrutika; Prakash, Sanjeevi; Arjunan, Vinuganesh; Kumar, Amit (Zootaxa, 2022)
A new species of marine amphipod, Protohyale covelongensis sp. nov., is described from India. The taxon is fully described and illustrated with which it could be easily identified morphologically. Protohyale covelongensis sp. nov. has a specific shape of the basis of pereopod 7 in the mature male, forming a distinct axe-shaped flange on its anterior margin. This characteristic feature serves to distinguish it from other Indian hyalid species. This new species is also compared with known species with which it could be confused. We have performed molecular phylogeny based on the mitochondrial gene cytochrome c oxidase subunit I.